Letter - Sadler, C. R.
Buy and read the "Assurance Agents' Chronicle." 2d. weekly from all Newsagents GENERAL SECRETARY W. SHEARD ESTABLISHED 1884. TELEPHONE: RUSHOLME 4759 NATIONAL AMALGAMATED UNION OF LIFE ASSURANCE WORKERS REGISTERED OFFICE: "Rossmoyne," 11 Mauldeth Road, Withington, Manchester, 20. Birmingham Central. BRANCH 11, Solihull Road, Sparkhill, Birmingham. 11. (Date as postmark) Branch No reply AC Dear Sir, The above branch instructed me to forward you the following resolution passed at their meeting held 9th April, 1942, reading as follows:- That this Branch urges you to approach the American Government to intervene in Vichy on the following points:- 1. To stop the extradition of former members of the International Brigade to Germany and German occupied countries and Italy. 2. To grant French exit permits to former International Brigaders. 3. To permit the distribution of relief to International Brigaders in French and Spanish internment camps by accredited relief organisations in France, Spain, Portugal and Switzerland. I may say this matter was passed without any dissent and therefore has the fullest possible backing, and we look forward to your support with confidence. Thanking you, Yours faithfully, C.R. Sadler. 292/946/34/34